Cyclic performance of different mitigation strategies proposed for segmental precast bridge piers. (February 2022) - Govahi, Ehsan; Salkhordeh, Mojtaba; Mirtaheri, Masoud
Abstract: Recent researches proved that the segmental precast post-tensioned bridge piers could sustain large deformations with minor residual drifts. Several studies were implemented to demonstrate the effect of different types of mitigation strategies on improving bridge piers' seismic behavior. However, a few studies are performed to examine the most effective mitigation strategy among these broad ranges of propositions. This paper presents a comparative study to examine the cyclic performance of segmental post-tensioned bridge columns (SPCs) equipped with four different mitigation strategies, including high-strength rebars (SPCHS), base seat angles (SPCSA), lead base-isolation (SPCI), and FRP tubes (SPCFRP). Besides, a monolithic specimen is considered as the reference specimen to assess the cyclic performance of other specimens. Three different bridge piers, including a conventional pier, a segmental pier with high-strength rebars, and a pier with an FRP-covered segment, are used to verify the modeling procedure. Results determine the high performance of the SPCFRP specimen in terms of low residual drifts as well as the lesser concrete damages. The SPCHS pier demonstrates the maximum lateral strength, but higher concrete damages occur in this specimen compared to the SPCFRP pier. Although the SPCSA pier shows the maximum energy dissipation, more residual drifts remain in this specimen than the SPC pier. It is pointed out that the SPCI specimen has slightly lessened the residual drifts and concrete damages compared to the SPC specimen.